Differential properties of the two Drosophila ?-tubulin isotypes. - Raynaud-Messina, B.; Debec, A.; Tollon, Y.; Gares, M.; Wright, M. (European Journal of Cell Biology, 2001)
The functional significance of distinct gamma-tubulins in several unrelated eukaryotes remains an enigma due to the difficulties to investigate this question experimentally. Using specific nucleotidic and immunological probes, we have demonstrated that the two divergent Drosophila gamma-tubulins, gamma-tub23C and gamma-tub37CD, are expressed in cultured cells. Gamma-tub37CD is constantly detected at the centrosome and absent in the mitotic spindle, while gamma-tub23C is extensively recruited to the centrosome during mitosis and relocalizes in the mitotic spindle. The two gamma-tubulins exhibit distinct biochemical properties. Gamma-tub23C is present in the soluble gamma-tubulin small complexes (10S) and gamma-tubulin big complexes (35S) and is loosely associated to the cytoskeleton. In contrast, gamma-tub37CD is undetectable in the soluble fraction and exhibits a tight binding to the centrosome. Syncytial embryos also contain the two gamma-tubulin isotypes, which are differentially recruited at the centrosome. Gamma-tub23C is present in the 10S soluble complexes only, while y-tub37CD is contained in the two soluble complexes and is recruited at the centrosome where it exhibits an heterogeneous binding. These results demonstrated an heterogeneity of the two Drosophila gamma-tubulin isotypes both in the cytoskeletal and the soluble fractions. They suggest the direct implication of the 35S complex in the centrosomal recruitment of gamma-tubulin and a conditional functional redundancy between the two gamma-tubulins.